Inside ethnography: researchers reflect on the challenges of reaching hidden populations - Boeri, Miriam; Shukla, Rashi K. (University of California Press, 2019)
Introduction /Miriam Boeri and Rashi K. Shukla --Going native with evil /Marie Rosenkrantz Lindegaard --Lost in the park : learning to navigate the upredictability of fieldwork /Elizabeth Bonomo and Scott Jacques --Unearthing aggressive advocacy : challenges and strategies in social service ethnography /Curtis Smith and Leon Anderson --Going into the gray : conducting fieldwork on corporate misconduct /Eugne Soltes --Hide-and-seek : challenges in the ethnography of street drug users /Merrill Singer and J. Bryan Page --Into the epistemic void : using rapid assessment to investigate the opioid crisis /Jason N. Fessel, Sarah G. Mars, Philippe Bourgois, and Daniel Ciccarone --Conducting international reflexive ethnography : theoretical and methodological struggles /Avelardo Valdez, Alice Cepeda, and Charles Kaplan --Hidden : accessing narratives of parental drug dealing and misuse /Ana Lilia Campos-Manzo --Navigating stigma : researching opioid and injection drug use among young immigrants from the former Soviet Union in New York City /Honoria Guarino and Anastasia Teper --Dangerous liaisons : reflections on a serial ethnography /Robert Gay --The emotional labor of fieldwork with people who use methamphetamine /Heith Copes --Ethnography of injustice : death at a county jail /Joshua Price --Conclusion : looking back, moving forward /Rashi K. Shukla and Miriam Boeri.